'What's my risk of sustaining an ACL injury while playing football (soccer)?' A systematic review with meta-analysis. Issue 21 (29th March 2018) - Montalvo, Alicia M; Schneider, Daniel K; Silva, Paula L; Yut, Laura; Webster, Kate E; Riley, Michael A; Kiefer, Adam W; Doherty-Restrepo, Jennifer L; Myer, Gregory D
Abstract : Objective: To estimate the incidence proportion (IP) and incidence rate (IR) of ACL injury in football players. Design: Systematic review with meta-analysis. Data sources: PubMed, CINAHL and SPORTDiscus electronic databases were searched from inception to 20 January 2017. Eligibility criteria for selecting study: Studies that reported the total number of participants/population by sex, total number of ACL injuries by sex and total person-time by sex were included. Results: Twenty-eight studies were included. The IP and IR of ACL injury in female football players were 2.0% (95% CI 1.2% to 3.1%) and 2.0/10 000 athlete exposures (AEs) (95% CI 1.6 to 2.6; I 2 =91%) over a period of one season to 4 years. The IP and IR of ACL injury in male players were 3.5% (95% CI 0.7% to 8.2%) and 0.9/10 000 AEs (95% CI 0.7 to 1.1; I 2 =94%). Studies that evaluated matched cohorts of female and male players showed no difference in IP (relative risk=1.2; 95% CI 0.9 to 1.6; P=0.47) over a period of one season to 4 years. Women were at greater risk than men (incidence rate ratio (IRR)=2.2; 95% CI 1.6 to 3.1; I 2 =83%; P<0.001). When accounting for participation level, the difference in IR between women and men was greatest for intermediate players (IRR=2.9; 95% CI 2.4 to 3.6) compared with amateur (IRR=2.6; 95% CI 1.4 to 4.8) and elite (IRR=2.0; 95% CI 1.1 to 3.4) players. Summary/conclusion: Overall, more men sustained ACL injury in football. There was no difference in the relative risk of ACL injury between female and male football players in a window that spanned one season to 4 years. The IR of ACL injury among women was 2.2 times higher than the IR of ACL injury among men. The reported sex disparity in ACL injury was independent of participation level.